Cover Image, Volume 44, Issue 10. (13th October 2021) - Ren, Na; Wang, Conghui; Zhao, Zhuo; Liang, Yajing; Wei, Wei; Qin, Guotong
Abstract : The cover image is based on the Original Article Recovery of ferulic acid from corn bran by adsorption on mesoporous carbon by Wei Wei et al., https://doi.org/10.1111/jfpe.13817 .